Engineering high quality medical software : regulations, standards, methodologies and tools for certification - Coronato, Antonio, 1972- (The Institution of Engineering and Technology, 2018)
This book focuses on high-confidence medical software in the growing field of e-health, telecare services and health technology. It covers the development of methodologies and engineering tasks together with standards and regulations for medical software.
Keywords: Medicine -- Computer programs.; Medicine -- Data processing.; Medical care -- Information technology.; Medical informatics.; elektronické knihy; electronic books